Crime and Punishment in Ghana: The Need for Security Sector Reforms - Tuffour, Kwadwo Addo; Adjanor, Cecilia (Universitas Muhammadiyah Surakarta, 2024)
It is incumbent on all governments the world over to provide security for the citizenry to develop their quality of life. Crime prevention strategies are therefore critical in achieving this laudable goal. Governments, security sector institutions and organizations encounter challenges in their quest to prevent crime in society. The prevention of crime has become a very significant national priority for public safety and security. Determining the main factors associated with the various criminal offences has the potential to lead to the development of strategies that can help prevent or reduce the incidence of crime. The laws of Ghana, especially the 1992 Republican Constitution uphold the respect for fundamental human rights, rule of law, fairness and lack of arbitrariness in the implementation of the law, especially in dealing with criminal offenders. The legal framework on criminal justice mandates institutions such as the Judicial Service, Ghana Police Service and the Prisons Service to ensure the prosecution and subsequent punishment of offenders. Improving democratic security sector governance (SSG) through security sector reform (SSR) is a key pre-requisite to achieving the ideals of crime prevention and punishment of offenders. Security sector reform aims to develop a secure environment for national development, good governance and community participation in crime prevention and punishment. This paper provides a comprehensive desk review of crime and punishment in Ghana from the perspective of the law and society and make appropriate recommendations for security sector reforms to enable the country achieve the objects of crime prevention. Semua pemerintah harus memberikan keamanan bagi warga negara untuk meningkatkan kualitas hidup mereka. Pencegahan kejahatan sangat penting untuk mencapai tujuan ini. Pemerintah, lembaga keamanan, dan organisasi harus berjuang untuk mencegah kejahatan. Pencegahan kejahatan merupakan tujuan utama keselamatan dan keamanan nasional. Mengidentifikasi penyebab utama tindak pidana dapat membantu mencegah atau mengurangi kejahatan. Tujuan dari penelitian ini adalah untuk menganalisis hukum di Ghana, terutama Konstitusi Republik 1992, untuk melindungi hak asasi manusia, supremasi hukum, keadilan, dan penegakan hukum yang tidak sewenang-wenang, terutama bagi pelaku. Lembaga Kehakiman, Kepolisian Ghana, dan Lembaga Pemasyarakatan harus menuntut dan menghukum para pelaku kejahatan di bawah hukum peradilan pidana. Penelitian ini menggunakan pendekatan penelitian yuridis normatif untuk mengkaji berbagai aturan tersebut. Hasil penelitian ini menunjukkan bahwa demokratisasi tata kelola sektor keamanan melalui reformasi sektor keamanan sangat penting untuk mencegah dan menghukum kejahatan. Analisis sosial dan hukum terhadap kejahatan dan hukuman di Ghana adalah tujuan dari artikel ini. Untuk memerangi tingkat kejahatan yang meningkat, sangat diperlukan teknik pencegahan kejahatan yang holistik dan terintegrasi di semua sektor ekonomi.